Debt limit, fiscal space and fiscal fatigue in the Central and Eastern European countries of EU - Aurel Iancu; Dan Olteanu (Romanian Academy, National Institute for Economic Research, 2023)
This study analyzes the correlation between the primary budget balance and the public debt over the last two decades, for a panel of 12 countries from Central and Eastern Europe, in order to assess their debt sustainability, the level of debt at which fiscal fatigue may occur, as well as the degree of risk of fiscal fatigue, depending on the past and future evolution of public debt. First, using estimates of the cubic fiscal reaction function and two variants (quadratic / linear) of the financing cost function, we determined the equilibrium level of public debt as percentage of GDP, the" fiscal fatigue" point and the debt limit, for the whole panel and for each country. Second, by using the common (from panel regressions) and country-specific coefficients, and public debt projection for 10 and 5 years, we evaluated the level of risk for fiscal fatigue, in relation to the future evolution of public debt and other financial indicators.
Keywords: H61; H62; H63; H68; E62; 330; primary balance; public debt; fiscal space; fiscal policy